A new species of the genus Eremias Fitzinger, 1834 (Squamata: Lacertidae) from Central Iran, supported by mtDNA sequences and morphology - Rastegar-Pouyani, Eskandar; Hosseinian, Saeed; Rafiee, Soolmaz; Kami, Haji Gholi; Rajabizadeh, Mehdi; Wink, Michael (Zootaxa, 2016)
A new species of the lacertid genus Eremias Fitzinger, 1834 is described from northwest of Isfahan province, Central Iran. Two mitochondrial genes (cyt b and 12S DNA) were sequenced and analyzed as reliable molecular markers for the separation of this newly discovered species from closely related species within the genus Eremias: E. velox, E. persica, E. papenfussi, E. lalezharica, E. montana, E. strauchi, E. kopetdaghica and E. suphani. Genetic distances (K2-p) between any of these species with the newly described species are relatively high (27.5–32.8% for cyt b and 5.2–10.4% for 12S DNA). Phylogenetic analyses (MP, ML and BI) generated trees with very similar topologies. According to molecular and morphological data, Eremias isfahanica sp. nov. belongs to the subgenus Aspidorhinus, and is closely related to E. papenfussi. Because several new Eremias species have recently been described from the Iranian Plateau, we additionally provide an updated identification key.